Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3399/bjgp12x654560
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical features of bladder cancer in primary care

Abstract: BackgroundBladder cancer accounts for over 150 000 deaths worldwide. No screening is available, so diagnosis depends on investigations of symptoms. Of these, only visible haematuria has been studied in primary care. AimTo identify and quantify the features of bladder cancer in primary care. Design and settingCase-control study, using electronic medical records from UK primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(111 citation statements)
references
References 24 publications
6
105
0
Order By: Relevance
“…Testing for association used univariable and multivariable conditional logistic regression, performed in three stages. [17][18][19][20] The variable for hypergammaglobulinaemia was not included in the multivariable analyses as it could be considered an outcome variable rather than an explanatory variable. The first stage, univariable analysis, used a P-value threshold of 0.1 or below to identify candidate variables for multivariable analysis.…”
Section: Analysis and Statistical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Testing for association used univariable and multivariable conditional logistic regression, performed in three stages. [17][18][19][20] The variable for hypergammaglobulinaemia was not included in the multivariable analyses as it could be considered an outcome variable rather than an explanatory variable. The first stage, univariable analysis, used a P-value threshold of 0.1 or below to identify candidate variables for multivariable analysis.…”
Section: Analysis and Statistical Methodsmentioning
confidence: 99%
“…19,20,[22][23][24] This study, the largest reported, provided ample power to identify rare but potentially clinically relevant symptoms of myeloma, and allowed sub-analyses by age. The results are highly likely to be generalisable.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…8 Moreover, the PPVs for visible haematuria were lower for renal cancer than for bladder cancer, and increased with repeat presentation in primary care (which the guideline development group considered a proxy for persistence) in both renal 13 and bladder cancer. 12 …”
Section: Trends In Urology and Men's Health March/april 2016mentioning
confidence: 99%
“…3 In general, the PPVs for visible haematuria increased with age in both cancers [11][12][13] and tended to be higher in males than in females. 4,8 In males, this started at 1% below 45 years of age, increasing to 4.4% (45-54 years), 8.5% (55-64 years), 11.2% (65-74 years), 10.3% (75-84 years) and 9.2% (85 years or above).…”
Section: Trends In Urology and Men's Health March/april 2016mentioning
confidence: 99%
See 1 more Smart Citation